Minimally Invasive Image‐Guided Cochlear Implantation for Pediatric Patients: Clinical Feasibility Study. (21st January 2014) - Balachandran, Ramya; Reda, Fitsum A.; Noble, Jack H.; Blachon, Grégoire S.; Dawant, Benoit M.; Fitzpatrick, J. Michael; Labadie, Robert F.
Abstract : Objective: Minimally invasive image‐guided cochlear implantation (CI) involves accessing the cochlea via a linear path from the lateral skull to the cochlea avoiding vital structures including the facial nerve. Herein, we describe and demonstrate the feasibility of the technique for pediatric patients. Study Design: Prospective. Setting: Children's Hospital. Subjects and Methods: Thirteen pediatric patients (1.5 to 8 years) undergoing traditional CI participated in this Institutional Review Board–approved study. Three fiducial markers were bone‐implanted surrounding the ear, and a CT scan was acquired. The CT scan was processed to identify the marker locations and critical structures of the temporal bone. A safe linear path was determined to target the cochlea avoiding damage to vital structures. A custom microstereotactic frame was fabricated that would mount on the fiducial markers and constrain a tool to the desired trajectory. After traditional mastoidectomy and prior to cochleostomy, the custom microstereotactic frame was mounted on the bone‐implanted markers to confirm that the achieved trajectory was safe and accurately accessed the cochlea. Results: For all the 13 patients, it was possible to determine a safe trajectory to the cochlea. Custom microstereotactic frames were validated successfully on 9 patients. Two of these patients had inner ear malformations, and this technique helped the surgeon confirm ideal location for cochleostomy. For patients with normal anatomy, the mean and standard deviation of the closest distance of the trajectory to facial nerve and chorda tympani were 1.1 ± 0.3 mm and 1.2 ± 0.5 mm, respectively. Conclusion: Minimally invasive image‐guided CI is feasible for pediatric patients.